PENGARUH PROPORSI BAHAN UTAMA (PUREE KACANG MERAH DAN TEPUNG TERIGU) DENGAN PUREE UBI MADU TERHADAP SIFAT ORGANOLEPTIK KUE LUMPUR - PUTRI HAPSARI, ADELYA (Jurnal Tata Boga, 2018)
Mud cake is a market snack based wheat flour that has sweet flavor. In this study, mud cake is made by proportioning the main ingredients (wheat flour and red bean puree), with honey sweet potato puree. This study aims to determine: 1) the effect of the proportion of red bean puree and wheat flour, with honey sweet potato puree against organoleptic characteristics and mud cake slurry level; 2) the best proportion of red bean puree mud cake and wheat flour, with honey sweet potato puree, and 3) nutrient content of mud cake which includes: carbohydrate, protein, fat, fiber and calcium. This research type is experimental research with 3 treatments, namely red bean puree 40%, 50%, and 60% in proportion of 48g, 60g, 72g, and 100% honey sweet potato puree amout 250g. The data were collected using observation sheet with 30-panelists consisting of 10 trained panelists and 20 semi-trained panelists. Data analysis using One Way Anava test, if any significant effect tested with DMRT (Duncan Multiple Renge Test) advanced test. The results showed: 1) there is influence of proportion of red bean puree and wheat flour, with puree of honey sweet potato puree onorganoleptic characteristics of mud cake included aroma, color, and taste; while in the mud cakes there is no effect in the texture and fondness level; 2) the best proportion of mud cake sare 60% red bean puree with amount of 72 g, 48 g wheat flour, and 250 g honey sweet potato puree; and 3) the nutrient content of mud cake from the best proportion is 8.73 g carbohydrate, 1.79 g protein, 4.63 g fat, 3.08% fiber, and 51.65 mg calcium. Keywords: Mud Cake, Red bean Puree, honey sweet potato puree, Wheat Flour, Organoleptic characteristics.